Ethical Principles, Process, and the Work of Bioethics Commissions - Sulmasy, Daniel P. (The Hastings Center report, 2017)
Shortly after the Presidential Commission for the Study of Bioethical Issues was constituted in 2010 and days before the commission members were to join a conference call to discuss possible topics for their deliberation, Craig Venter held a press conference announcing that his lab had created a synthetic chromosome for a species of mycoplasma and had inserted this genetic material into organisms of another species of mycoplasma (the genes of which had been deactivated), transforming the host species into the donor species. While not overtly claiming to have “created life in the test tube,” Venter's publicity seemed cleverly designed to provoke the media into reporting his discovery in just that way. The resulting uproar caused President Obama to give his new bioethics commission the assignment of investigating the ethics of the emerging field of synthetic biology. The commission went right to work. It formed working groups to deliberate about parts of the report, feeding ideas and language to the staff members who would do the actual writing, and then present the working group suggestions to the commission as a whole for public deliberation at open meetings. One of those working groups was charged with coming up with ethical principles that would guide the analysis. Having served as a member of that working group, I report here on the process by which these principles emerged and reflect upon the suitability of that process for the work of public bioethics commissions.